Migrating sandwaves riding on relict dunes of Taiwan shoal, northern South China Sea - Yang, Yuping; Liu, Meng; Xu, Jingping; Xu, Weikun (Frontiers in Earth Science, 2022)
Sandwaves, a ubiquitous bedform commonly found in most coastal seas and sometimes in deep waters of continental slopes and submarine canyons, are often the subject of marine hazard studies because their frequent migration can pose potential threats to pipelines or other engineering structures in the ocean. Analyses of high-resolution bathymetric data collected along a 136-km multibeam bathymetric survey line demonstrate the co-existence of three different sizes of sandwaves: giant, primary dunes (~10-15 m in height, up to 2,000 m in length); small, secondary sandwaves (~1 m in height, ~50 m in length) riding on the stoss side of the primary dunes; and mid-size dunes (~5-10 m in height, ~100-500 m in length) found in the trough of primary dunes. While the tidal current-driven, secondary sandwaves are migrating, the primary and mid-size dunes are immobile. Empirical model results suggest that the primary dunes are relict dunes that formed in geologic past when sea level was higher or the seabed elevation was lower.